Description of human infestations by ticks in Panama and Costa Rica - Sergio Bermúdez; Vicente Greco-Mastelari; Yamitzel Zaldívar; Michelle Hernández; Lillian Domínguez A.; Victor M. Montenegro H.; José M. Venzal (Microbes, Infection and Chemotherapy, 2021)
Tick bites in humans are associated with the transmission of pathogens, anaphylactic shock, paralysis, and secondary infections. In this work we described six cases of tick bites in patients from Panama and Costa Rica. These bites were provoked for adults of Ornithodoros puertoricensis, Amblyomma cf. oblongoguttatum, Amblyomma ovale, and Ixodes cf. boliviensis, and a nymph of Amblyomma mixtum. The relationships of these species of ticks with the environment are explained. Among the reactions observed in the patients there are blisters, maculo-papular rash, granuloma, lymphadenopathy, and erythema migrans-like rash, but none referred symptoms compatible with an infectious disease. In the collected ticks a PCR battery was developed to rule out Borrelia, Rickettsia, Anaplasmataceae, and Coxiella diseases to the ticks from the cases 1, 2, 3 and 4, with negative results. Although no pathogen infections were evidenced, these finding indicate that the tick bites constitute a public health problem what goes unnoticed in many countries.